Evaluation of the effect of antimicrobials in marine cultures, using the copepod Acartia tonsa as a bioindicator. Issue 8 (14th September 2018) - de Palma Lopes, Laís Fernanda; Agostini, Vanessa Ochi; Guimarães, Sanye Soroldoni; Muxagata, Erik
ABSTRACT: Cultures of the copepod Acartia tonsa are used both in aquaculture and ecotoxicology studies. However, the cultivation of these crustaceans at high densities results in the proliferation of microorganisms that can affect the organisms of interest, leading to illness or death. Antimicrobials inhibit microbial growth and may favour the cultivated species, aiding the development of ecological studies. This study investigated the potential of antimicrobials (antibiotic + antifungal) to inhibit bacteria and fungi when applied to marine zooplankton cultures, using the copepod A. tonsa as a bioindicator of acute toxicity. Treatment with 0.025 g L −1 of penicillin G potassium + 0.08 g L −1 of streptomycin sulphate + 0.04 g L −1 of neomycin sulphate + 0.005 g L −1 of nystatin resulted in 95% bacterial inhibition (after 12 h of exposure); however, after this time, the inhibitory effect was lost. The antimicrobial combination tested in this study prevented colonisation by fungi until 168 h after exposure, without causing acute toxicity to A. tonsa. Thus, it has potential for use in marine cultures of less sensitive organisms.